STUDY OF THE PREBIOTIC CONCENTRATE DOSE INFLUENCE ON THE EFFICIENCY OF SKIM MILK FERMENTATION BY LACTIC ACID MICROORGANISMS - Aleksey Lodygin; Elena Medintseva; Dmitriy Lodygin (Вестник Северо-Кавказского федерального университета, 2022)
MICROORGANISMS Modern trends of functional foods technology development are observed. The relevance of fermented dairy products enriched with prebiotic concentrate production is grounded. Composition and organoleptic and microbiologic attributes of prebiotic concentrate on the base of skim milk permeate are presented. Organoleptic attributes offermented skim milk with addition of prebiotic concentrate in comparison with control samples are tested. The influence of the prebiotic concentrate dose on lactic acid production efficiency by Lbc. bulgaricus, Str. thermophilus and Lbc. acidophilus starter cultures is studied. The optimal dose of prebiotic concentrate is established.